PENGARUH BAMBOO EXERCISE TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DI PUSKESMAS CUKIR, INDONESIA The Influence of Bamboo Exercise to Reducing High Blood Pressure Among Elder People in Primary Health Care (PHC) of Cukir, Jombang - Urifah, Siti; Ninuk, Devin Prihar (JURNAL NERS LENTERA, 2018)
Introduction: Hypertension is one of non-communicable disease and this disease also one of leading killer if they did not get early treatment and early prevention. Mostly Hypertension was among elder people, many factors which influence this disease, such as heredity, eating behavior with high salt, obesity and lowest physical activities. Because of that physical activity like regular exercise can prevent of hypertension complication. The aim of this study was to assess the influence of Bamboo Exercise to reducing high blood pressure among elderly in PHC of Cukir, Jombang. Methodology: the methodology of this reseach used pra experimet with pre-post test desain, the population of this reseach was elderly who had hypertention. 124 respondents was selected by using inclusion criteria. The inclusion criteria are elder people who have hypertension at least six months ago, elderly aged 55 years old or more and elderly who did not consume hypertension medition when attanding this reseach. The data analyzed by t-test with α = 0,05. Results and dscussion: the results of this study found that the ages of elederly ranged from 55-75 years old with the mean of 60.3 years and standard deviation of 6.6 years. The majority of elderly were female (74.1%), and almost half of those had elementary school as their highest education (48,4%) and more than half of the participants were not work as their employment (54,1%). Based on t-test found that there is influence of Bamboo Exercise to Reducing High Blood Pressure Among Elder People in Primary Health Care (PHC) of Cukir, Jombang (p-value 0.001 and t=30.0 ; p-value 0.001 and t=3.7). The quality of life and life expectacy of elderly people was special attantion in goverment, because life expectacy is one of indicator for successful national development. Because of that the prevention of degeneratif disease like hypertention is very importance issues among elder people.